KEMANDIRIAN PERSONAL HYGIENE ANAK USIA 7 - 12 TAHUN SEBELUM DAN SESUDAH DIBERIKAN PROMKES DI SMPN N 1 RAMBAH KABUPATEN ROKAN HULU - Romy Wahyuny; Andria; Ermiza (Fakultas Ilmu Kesehatan, 2021)
Personal Hygiene personal is an individual's efforts to maintain their cleanliness and health, both physically and mentally. Look clean, fragrant, and neat are very important dimensions in measuring the level of individual welfare in general. The purpose of this study was to see the independence of personal hygiene in children aged 7-12 years before and after being given promkes at SMP N 1 Rambah, Rokan Hulu Regency. The research design is a quasiexperimental research with a time series design approach with a total sample of 10 people. The results of this study there is a significant difference between the mean of children's independence before and after being given Promkes (p = 0.000). It is recommended for students of SMP N 1 Rambah, Rokan Regency to be able to use the results of this study as information to increase children's independence in caring for their own hygiene.